Morphological and cytological characteristics of cytoplasmic male sterility system 09-05A in spring stem mustard (Brassica juncea var. tumida Tsen et Lee) - WANG Jie; REN Xiliang; HUANG Yunping; AN Xuejun; GAO Tianyi; MENG Qiufeng (浙江大学学报. 农业与生命科学版, 2018)
Cytoplasmic male sterility (CMS) 09-05A is a new CMS line in spring stem mustard that is transferred from oxa A CMS. In this study, morphological and cytological observation of anther and pollen grain of 09-05A CMS was carried out by scanning electron microscopy and transmission electron microscope. It was revealed that the microspore abortion were initiated at the uninucleate stage. The cell nucleus and other cellular components of microspores were degraded to form collapsed and abortive pollen grains eventually during the pollen development. This study clarified the abortive stage and cytological characteristics, which may help to uncover the developmental mechanism of CMS 09-05A and provide a theoretical basis for the heterosis utilization of CMS in stem mustard (Brassica juncea var. tumida Tsen et Lee).